UPAYA KOMISI PEMILIHAN UMUM (KPU) KABUPATEN TUBAN DALAM PENINGKATAN PARTISIPASI POLITIK MASYARAKAT - Moh Wazid Husni; Harmanto Harmanto (Kajian Moral dan Kewarganegaraan, 2021)
The aim of the research is to describe the efforts of the Tuban district general election commission in increasing public participation. In the 2019 elections, the level of public participation in politics increased. The number of abstentions is decreasing, and the public's concern for the political conditions in the country is increasing. There is an increase in public participation in politics due to the efforts made by the General Election Commission which is carried out in each region. As in Tuban district, it was noted that in the 2019 elections the level of public participation increased in the general election. The increase in public participation in the elections was based on the efforts made by the Tuban district election commission. This study used a qualitative method with a descriptive design. The data obtained were in the form of interviews conducted online and face to face with five informants who met the specified criteria. The data validity technique used was source triangulation. The results of the study explained that the efforts made by the Tuban district general election commission were political socialization, political education for first-time voters and the formation of democratic volunteers. Based on the theory used, namely the political behavior learning theory that political education can influence the attitude or behavior of each individual in political participation. According to the research results, it was found that the increase in political participation of the Tuban people was influenced by several activities or programs organized by the general election commission in the district. Keywords:General election commission, Politic Participation, Politic education